Applied Study to Evaluate and Rehabilitate Schools Affected by the War on Syria - فايز علي جراد, (Latakia University Journal -Engineering Sciences Series, 2023)
The terrorist war on Syria left a large amount of destruction in terms of both infrastructure and buildings, as the number of damaged buildings reached large numbers in a large number of Syrian cities, and part of those buildings were school buildings, so a large part of these buildings must be demolished because they are not The validity of its use and another section, the percentage of damage to it was small, and this building can be repaired and strengthened. In this research, a framework was developed to evaluate the damaged school buildings and to determine the overall damage percentage of the building by evaluating the structural elements of the building and determining the degree of damage for each of them, through the field study and tests, leading to the structural analysis, where the Etaps program was used, and in the end, appropriate reinforcement methods were used for each A case of the structural elements and as an applied study of the framework, work was done on the case study, which is a school building in Lattakia Governorate, Aramo region, to document the method of study and the reinforcement used.